PEDAGOGICAL PROBLEMS OF DEVELOPING PERSONAL QUALITIES SIMILAR TO PROFESSIONAL ACTIVITY IN STUDENTS - Khushnazarova Mamura Nodirovna (Journals Park Publishing, 2024)
In this article, the formation of true humanitarianism in students, basic knowledge about the nature of people, the ability to evaluate their positions in relation to life, social environment and existence, based on the knowledge, observations, experience and conclusions acquired outside the institutions of science, interdisciplinary and higher education. was discussed.
Keywords: pedagogical culture, scientific and innovative thinking, axiological attitude, value system, motives of activity, axiological criterion, humanization of education, professional competence.